Vitamin D Regulates the Expression of Glucocorticoid Receptors in Blood of Severe Asthmatic Patients. (6th August 2021) - Mahboub, Bassam; Al Heialy, Saba; Hachim, Mahmood Yaseen; Ramakrishnan, Rakhee K.; Alzaabi, Ashraf; Seliem, Rania Medhat; Salameh, Laila Ibraheem; Toor, Sameen Masooma; Shendi, Fathelrahman Salem; Al Ali, Ola Mohamed; Safarini, Basil Khalid; Erabia, Wafa Taleb; et al.
Abstract : Purpose . Vitamin D (VitD) deficiency is a significant public health concern in many areas around the globe and has been associated with many immune-mediated diseases, including asthma. Severe asthma has been linked to a decreased glucocorticoid receptor (GR) ratio (GR- α /GR- β ratio), indicating steroid hyporesponsiveness. Using a combination of in silico and in vivo approaches, we aimed to explore the immunomodulatory effect of VitD on asthmatic patients diagnosed with hypovitaminosis D. Methods . In silico tools were used to identify the regulatory effect of VitD supplementation on GR genes. We measured the expression levels of GR- α and the inactive isoform, GR- β, in the blood of adult asthmatics diagnosed with hypovitaminosis D before and after VitD supplementation. Moreover, the blood levels of inflammatory cytokines associated with asthma severity were determined. Results . Using an in silico approach, we identified specific genes commonly targeted by VitD as well as corticosteroids, the mainstay of asthma therapy. NR3C1 gene encoding GR was found to be significantly upregulated on Th2 CD4 cells and NK cells. Interestingly, blood expression level of NR3C1 was lower in severe asthmatics compared to nonsevere asthmatics and healthy controls, while the blood level of VitD receptor (VDR) was higher. Upon VitD supplementation of severe asthmatic patients, there was a significant increase in the blood levels of GR- α with no change in GR- β mRNA expression. VitD supplementation also suppressed the blood levels of IL-17F and IL-4. Conclusion . VitD may enhance steroid responsiveness by upregulating the expression of steroid receptor GR- α .